Faktor-Faktor yang berhubungan dengan Status Gizi Anak Balita di Rumah Sakit Umum Daerah Kabupaten Muna Tahun 2015 - Dingis, Apriani; Nofitasari, Ari (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
The nutritional status of children under five is an important matter that must be considered more deeply because it is based on the fact that toddlers are the age group that most often suffers from malnutrition (KKP) and is irreversible (cannot recover). Based on the results of a preliminary survey at the Regional General Hospital of Muna Regency, it was found that in 2013 the number of sufferers of malnutrition was 18 toddlers and in 2014 the number of sufferers of malnutrition was 28 toddlers. Then in the 2015 period from January to May the number of sufferers of malnutrition was 39 children under five. The purpose of this study was to determine the factors associated with the nutritional status of children under five at the General Hospital of Muna Regency. The type of research used is analytical research method with a cross sectional study approach. Sampling used the total sampling method and the number of samples was 39 respondents. The results showed that there was a weak relationship (phi = 0.378) between nutrient intake and the nutritional status of children under five (X² hit = 5.574 > X² tab = 3.841), there was a strong relationship (phi = 0.799) between mother's knowledge and child's nutritional status. under five years old (X² hit = 24,927>X² tab = 3.841), there is a strong relationship (phi = 0.742) between family income and nutritional status of children under five (X² hit = n21,474> X² tab = 3.841). It is recommended to the Munaagar District General Hospital to hold outreach to the community, especially mothers of toddlers about the need for nutritional intake for children under five.